PERENCANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK BERKEBUTUHAN KHUSUS - Rosyida Nurul Anwar; Zaenullah Zaenullah (UNIVERSITAS PGRI MADIUN, 2020)
Learning becomes programmed and planned activities in student meetings through professional competence, trustworthiness, social, and pedagogical. Children with special needs have different characteristics from normal children in general so that children with special needs Religious skills in children with special needs as a foundation for the faith. The purpose of this research is to study and analyze Islamic learning planning in children with special needs in kindergartens. This type of descriptive research using qualitative research methods in this study. Data collection uses interviews, collection, and collection. Research data are classified as primary data and secondary data. Data analysis techniques using data collection analysis, data reduction, data presentation, and conclusion collection. PAI in children with special needs is done by adjusting the government curriculum and school specificity, namely character, by involving all components of the school, namely students, learning objectives, learning resources, and learning outcomes.